PERANCANGAN SISTEM INFORMASI MANAJEMEN WAREHOUSE BERBASIS INTRANET DALAM PENYIMPANAN DAN PERSEDIAAN MATERIAL PADA PT.LEN INDUSTRI (PERSERO) BANDUNG - Tono Hartono (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2011)
Along with the rapid advancement of information technology today, information is very important in running a job and activities. Information is an element that has links the management functions of planning, operation, and control, without any instance information were can not run the operations of an instance well. Information availability of material being consideration of administrative division in making the decision to order material for production. The purpose of this study was to find out how the admission procedure, expenditures, requests, and ordering raw materials that are being run in PT. Len Indutri (Persero)Bandung, helping institutions to enhance effectiveness in conducting the inventory data processing to minimize the possibility of error that occurred, and making the application warehouse management system concerning inventory material, The result of this study is expected to be useful and serve as a material consideration in efforts to repair problems associated with the warehouse management Information System at PT. Len Industri (Persero) Bandung.The method used in the design of a structured approach based informationsystem. In the application system development phase, the author uses the classicalor a waterfall method, a tool used to design systems such as Data Flow Map, Context Diagram, Data Flow Diagrams, Data Dictionary, Normalization, Entity Relationship Diagram, Relationship Table, and the structure of files. Data collect techniques by observation, interview and documentation. While supporting software using MySQL as database and programming language HTML, JavaScript, and php.The results of research by the author are to produce an inventory information system to support corporate development and assist the monitoring and making of transaction report which quickly, precisely and accurately